Comparative Safety of Antiseizure Medication Monotherapy for Major Malformations. Issue 3 (12th December 2022) - Cohen, Jacqueline M.; Alvestad, Silje; Cesta, Carolyn E.; Bjørk, Marte‐Helene; Leinonen, Maarit K.; Nørgaard, Mette; Einarsdóttir, Kristjana; Engeland, Anders; Gissler, Mika; Karlstad, Øystein; Klungsøyr, Kari; Odsbu, Ingvild; et al.
Abstract : Objective: This study was undertaken to examine the comparative safety of antiseizure medication (ASM) monotherapy in pregnancy with respect to risk of major congenital malformations (MCMs), overall and by MCM subtype. Methods: We conducted a population‐based cohort study using national health register data from Denmark, Finland, Iceland, Norway, and Sweden (1996–2020). We compared pregnancies with first trimester exposure to lamotrigine monotherapy to ASM‐unexposed, carbamazepine, valproate, oxcarbazepine, levetiracetam, and topiramate to lamotrigine monotherapy, and stratified monotherapy groups by dose. The outcome was nongenetic MCM and specific subtypes. We estimated adjusted risk ratios (aRRs) and 95% confidence intervals (CIs) with log‐binomial regression and propensity score weights. Results: There was a higher crude risk of any MCM in pregnancies exposed to lamotrigine monotherapy (n = 8, 339) compared to ASM‐unexposed pregnancies (n = 4, 866, 362), but not after confounder adjustment (aRR = 0.97, 95% CI = 0.87–1.08). Compared to lamotrigine, there was an increased risk of malformations associated with valproate (n = 2, 031, aRR = 2.05, 95% CI = 1.70–2.46) and topiramate (n = 509, aRR = 1.81, 95% CI = 1.26–2.60), which increased in a dose‐dependent manner. We found no differences in malformation risk for carbamazepine (n = 2, 674, aRR = 0.91, 95% CI = 0.72–1.15), oxcarbazepine (n = 1, 313, aRR = 1.09, 95% CI = 0.83–1.44), or levetiracetam (n = 1, 040, aRR = 0.78, 95% CI = 0.53–1.13). Valproate was associated with several malformation subtypes, including nervous system, cardiac, oral clefts, clubfoot, and hypospadias, whereas lamotrigine and carbamazepine were not. Interpretation: Topiramate is associated with an increased risk of MCM similar to that associated with valproate, but lower doses may mitigate the risks for both drugs. Conversely, we found no increased risks for lamotrigine, carbamazepine, oxcarbazepine, or levetiracetam, which is reassuring. ANN NEUROL 2023;93:551–562